Normal and glaucomatous outflow regulation. (May 2021) - Acott, Ted S.; Vranka, Janice A.; Keller, Kate E.; Raghunathan, VijayKrishna; Kelley, Mary J.
Abstract: Glaucoma remains only partially understood, particularly at the level of intraocular pressure (IOP) regulation. Trabecular meshwork (TM) and Schlemm's canal inner wall endothelium (SCE) are key to IOP regulation and their characteristics and behavior are the focus of much investigation. This is becoming more apparent with time. We and others have studied the TM and SCE's extracellular matrix (ECM) extensively and unraveled much about its functions and role in regulating aqueous outflow. Ongoing ECM turnover is required to maintain IOP regulation and several TM ECM manipulations modulate outflow facility. We have established clearly that the outflow pathway senses sustained pressure deviations and responds by adjusting the outflow resistance correctively to keep IOP within an appropriately narrow range which will not normally damage the optic nerve. The glaucomatous outflow pathway has in many cases lost this IOP homeostatic response, apparently due at least in part, to loss of TM cells. Depletion of TM cells eliminates the IOP homeostatic response, while restoration of TM cells restores it. Aqueous outflow is not homogeneous, but rather segmental with regions of high, intermediate and low flow. In general, glaucomatous eyes have more low flow regions than normal eyes. There are distinctive molecular differences between high and low flow regions, and during the response to an IOP homeostatic pressure challenge, additional changes in segmental molecular composition occur. In conjunction with these changes, the biomechanical properties of the juxtacanalicular (JCT) segmental regions are different, with low flow regions being stiffer than high flow regions. The JCT ECM of glaucomatous eyes is around 20 times stiffer than in normal eyes. The aqueous humor outflow resistance has been studied extensively, but neither the exact molecular components that comprise the resistance nor their exact location have been established. Our hypothetical model, based on considerable available data, posits that the continuous SCE basal lamina, which lies between 125 and 500 nm beneath the SCE basal surface, is the primary source of normal resistance. On the surface of JCT cells, small and highly controlled focal degradation of its components by podosome- or invadopodia-like structures, PILS, occurs in response to pressure-induced mechanical stretching. Sub-micron sized basement membrane discontinuities develop in the SCE basement membrane and these discontinuities allow passage of aqueous humor to and through SCE giant vacuoles and pores. JCT cells then relocate versican with its highly charged glycosaminoglycan side chains into the discontinuities and by manipulation of their orientation and concentration, the JCT and perhaps the SCE cells regulate the amount of fluid passage. Testing this outflow resistance hypothesis is ongoing in our lab and has the potential to advance our understanding of IOP regulation and of glaucoma.